VLOG : A TOOL FOR STUDENTS’ SPEAKING PRACTICE ENHANCEMENT - Anggraeni, Anita; Rachmijati, Cynantia; Apriliyanti, Dewi Listia (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
Vlog, stands for video-blogging, is quite popular in the internet. Vlog also can be used as a learning tool especially for speaking skills. Therefore this research focuses on speaking skill via vlog to see the improvement of students? speaking skill. The method of this research was mixed methods. The research subjects were 13 vlogs made by students on the topic of spot tourism. The 13 vlogs were by assessed using the rubric developed by Dan Rooney (1998). The result found out that using vlog deemed to be improving students? speaking skill especially in the area of vocabulary, fluency, pronunciation and intonation. However the most common mistakes found are the way they delivered the introduction, how to form conclusions and the last is the grammatical structure. The findings of the research conclude that the application of vlog to improve students? speaking skill found to be successful with a positive perception from students as learning tool.